Pterostilbene 4′-β-Glucoside Attenuates LPS-Induced Acute Lung Injury via Induction of Heme Oxygenase-1. (23rd October 2018) - Park, Jeongmin; Chen, Yingqing; Zheng, Min; Ryu, Jinhyun; Cho, Gyeong Jae; Surh, Young-Joon; Sato, Daisuke; Hamada, Hiroki; Ryter, Stefan W.; Kim, Uh-Hyun; Joe, Yeonsoo; Chung, Hun Taeg
Abstract : Heme oxygenase-1 (HO-1) can exert anti-inflammatory and antioxidant effects. Acute lung injury (ALI) is associated with increased inflammation and influx of proinflammatory cells and mediators in the airspaces and lung parenchyma. In this study, we demonstrate that pterostilbene 4 ′ - β -glucoside (4-PG), the glycosylated form of the antioxidant pterostilbene (PTER), can protect against lipopolysaccharide- (LPS-) or Pseudomonas aeruginosa- (P. aeruginosa -) induced ALI when applied as a pretreatment or therapeutic post-treatment, via the induction of HO-1. To determine whether HO-1 mediates the antioxidant and anti-inflammatory effects of 4-PG, we subjected mice genetically deficient in Hmox-1 to LPS-induced ALI and evaluated histological changes, HO-1 expression, and proinflammatory cytokine levels in bronchoalveolar lavage (BAL) fluid. 4-PG exhibited protective effects on LPS- or P. aeruginosa- induced ALI by ameliorating pathological changes in lung tissue and decreasing proinflammatory cytokines. In addition, HO-1 expression was significantly increased by 4-PG in cells and in mouse lung tissues. The glycosylated form of pterostilbene (4-PG) was more effective than PTER in inducing HO-1 expression. Genetic deletion of Hmox-1 abolished the protective effects of 4-PG against LPS-induced inflammatory responses. Furthermore, we found that 4-PG decreased both intracellular ROS levels and mitochondrial (mt) ROS production in a manner dependent on HO-1. Pharmacological application of the HO-1 reaction product carbon monoxide (CO), but not biliverdin or iron, conferred protection in Hmox-1 -deficient macrophages. Taken together, these results demonstrate that 4-PG can increase HO-1 expression, which plays a critical role in ameliorating intracellular and mitochondrial ROS production, as well as in downregulating inflammatory responses induced by LPS. Therefore, these findings strongly suggest that HO-1 mediates the antioxidant and anti-inflammatory effects of 4-PG.